KEPUASAN KERJA: GAMBARAN UMUM DAN ANALISIS BIBLIOMETRIK - Erine, Octika; Juliana, Ahmad (Journal for Management Student (JFMS), 2024)
In human resource management, job satisfaction is one of the most important factors that must be considered in a company or organization. Job satisfaction refers to how satisfied or dissatisfied a worker is with their job as a result of various factors that affect their motivation. The purpose of this study is to learn more about job satisfaction variables. In achieving this goal, the researcher uses bibliometric analysis techniques by taking journals from Scopus and Google Scholar for the last ten years, from 2014-2024. The results of data filtering through Publish or Perish resulted in 500 (five hundred) articles collected. The results of this study found that there are 4 (four) categories that explain several variables related to job satisfaction, including leadership, salary, organizational commitment, and work stress. Overall, this study is expected to be a good reference for future research, especially for those who learn about job satisfaction.